Multiparticulate Drug Delivery System for Gastrointestinal Tuberculosis (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Drug solubility poses numerous challenges in design of formulations for drugs with poor aqueous solubility. Ethionamide is an antitubercular drug belonging to biopharmaceutical classification system class II drug having less aqueous solubility. Nanosuspensions were prepared by using various solvents such as methanol, ethanol, acetone and chloroform and it was prepared using anti-solvent precipitation technique by using probe sonication. Various stabilizers such as tocopherolpolythytlene glycol succinate, polyvinylpyrrolidone and tween 80 singly or in combination were studied. A 32 factorial design was employed to study the effect of independent variables, concentration of stabilizers and stirring speed on particle size and cumulative percent drug release. The particle size of the optimized batch was 97.54 ± 8.47 nm with polydispersity index of 0.36 and zeta potential -10.1 ± 2.3 mV. The cumulative percent drug release of optimized batch was found to be 95.01 ± 1.16% in 60 min. Optimized batch was ultracentrifuged and evaluated for saturation solubility studies, stability and powder X-ray Diffraction studies. Optimized nanosuspension was loaded on Espheres by spraying in a coating pan and then coating of Eudragit controlled release polymers. The coated Espheres were evaluated for drug content, friability, scanning electron microscopy, ex-vivo permeation studies and drug release kinetics studies. The friability value for primary coated sphere was found to be 0.8 ± 0.12% and for secondary was 1% and the best fit model was found to be Korsmeyer-Peppas model which is indicative of diffusion controlled release. Ex vivo diffusion studies revealed a moderate increase in permeability.